Technical and physical match demands of a NCAA Division I soccer goalkeeper - Spalding, J. (Electronic Theses and Dissertations, 3176, 2017)
The purpose of this study was to provide a better understanding of the goalkeeper position in order to prepare goalkeepers for competition. The objectives of this study were to characterize the technical and physical demands of an NCAA Division I collegiate goalkeeper over three seasons and examine trends from season to season. Count and frequency for each definition were analyzed. Results show that although the goalkeeper`s technical demands were characterized by engaging in play without action and being in the goal area, the gradually increased use of the feet over three season`s hints on the importance of skills performed with the lower body. Findings suggest that most shots faced by the goalkeeper were from direct attacks, outside the box and from central positions. Foot skills may be relied on with increasing experience. Over the course of three seasons, forward and lateral movements were the most common and second most common.